2023
DOI: 10.1088/1758-5090/ad04fe
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3D-printing bilayer GelMA-based hydrogel containing BP, β-TCP and exosomes for cartilage–bone integrated repair

Ting Sun,
Zhiqiang Feng,
Wenpeng He
et al.

Abstract: The integrated repair of cartilage and bone involves the migration and differentiation of cells, which has always been a difficult problem to be solved. We utilize the natural biomaterial gelatin to construct gelatin methacryloyl (GelMA), a hydrogel scaffold with high cell affinity. GelMA is mixed with different components to print a bi-layer porous hydrogel scaffold with different modulus and composition in upper and lower layers through 3D printing technology. The upper scaffold adds black phosphorus (BP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Col II is one of the most important components in cartilage tissue, responsible for maintaining the structure and function of cartilage. 57,58 The experimental data indicated that the mRNA levels of SOX 9, ACAN, and Col II in chondrocytes significantly increased in the POC/GATP composite scaffolds compared to the pure POC scaffold group by day 14 (Figure 7A−C). Importantly, among all of the composite scaffolds, the POC/10% GATP and POC/15% GATP scaffolds exhibited higher expression of SOX 9, ACAN, and Col II.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Col II is one of the most important components in cartilage tissue, responsible for maintaining the structure and function of cartilage. 57,58 The experimental data indicated that the mRNA levels of SOX 9, ACAN, and Col II in chondrocytes significantly increased in the POC/GATP composite scaffolds compared to the pure POC scaffold group by day 14 (Figure 7A−C). Importantly, among all of the composite scaffolds, the POC/10% GATP and POC/15% GATP scaffolds exhibited higher expression of SOX 9, ACAN, and Col II.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In vitro assays validated the scaffold's capability to improve osteogenesis and chondrogenic differentiation. Furthermore, in a rabbit model of cartilage-bone injury, MRI and micro-CT outcomes demonstrated that the 3D-printed bi-layer GelMA composite scaffold exhibited reparative effects closely mimicking normal tissue [205].…”
Section: D Printing/bioprinting In Tissue Engineeringmentioning
confidence: 96%